Teaching mathematics according to the strategy of the six hats of thinking: a practical model for a lesson in mathematics for the first year of average - Kahoul, Chafika; Ghediri, Maroua (Journal of Human Sciences, 2022)
“SIX THINKING HATS” One of the most important thinking programs developed by Edward de Bono divides human thinking into six patterns and each symbol pattern in a certain color (white-red-black-yellow-green-blue), fake hats symbolizing the way of thinking And learn how to coordinate the various factors to reach the creative thinking, and where the perception of the educational process of learning has changed and the role of teacher and learner has become a change in the strategies used in teaching in general and mathematics, Especially that mathematics is a part of our lives and has a great role in the language of science, so we aim through this paper to propose a teaching model according to the strategy of the six hats.